Application of immunofluorescence to a study of measles. Issue 6 (June 1976) - Mcquillin, J; Bell, T M; Gardner, P S; Downham, P S
Abstract : A new and rapid method for the laboratory diagnosis of measles, using the fluorescent antibody technique applied to nasopharyngeal secretions is described. The reliability of the method was best shown by correlation with clinical diagnosis, which gave an overall agreement of 95% in 53 cases of typical clinical measles and 72 control children. Correlation with results of tissue culture and serology was also good, though these methods are in practice too infrequently successful to be used as the main standards of reliability. The antiserum used for immunoflorescence showed no cross-reactivity with other viruses. Viruses could be identified by the fluorescent antibody technique from 4 days before to 10 days after the onset of the rash in a high proportion of cases. The wider applications of this method include rapid diagnosis of measles before the rash has appeared; in cases where clinical diagnosis is in doubt, especially in dark-skinned children, or when the illness has been modified by previous vaccination; prevention of cross-infection by early detection of measles; and investigation of the immune response and its relationship to nutritional status.